DIGITAL CURRENCY MANAGEMENT, CIRCULATION AND TAXATION REGIME IN INDIA - MUNAGEKAR, AMEYA VILAS (Global journal of Business and Integral Security, 2022)
Money is always of the utmost significance to humanity and the economy. The global economy is persistently revolving around money. Man discovered fiat money through numerous stages, which resulted in many benefits and many drawbacks for humanity at the same time. There is no efficient traceability of dealings in fiat money, which was the prevalent drawback of this invention. It is hypothetically possible for any government to print cash to fill an economic deficit while overlooking the fact that paper money needs to be backed to qualify as a valued currency. Therefore, to avoid further catastrophe, countries should switch from fiat money to digital currency. Digital currency and cryptocurrencies, such as bitcoin, are more likely to prevent fraud, retain better records, and assist people in managing their money more efficiently. Because it is a virtual currency. Digital currency is an excellent solution to address concerns such as the non-traceability of financial transactions and counterfeit transactions, and it has the potential to both increase the tax base and lower the tax percentage at the same time. It is critical to adhere to the components of modern society and to change to improve society. Thus, the research focuses on the future of digital currency, its necessity, its good impacts, and its beneficial effects on the Indian economy and taxation. The study also looks into the circulation, management, and taxation regime of digital currency in India.